Heteroclinic path to spatially localized chaos in pipe flow - Budanur, Nazmi B; Hof, Björn (Journal of Fluid Mechanics)
In shear flows at transitional Reynolds numbers, localized patches of turbulence, known as puffs, coexist with the laminar flow. Recently, Avila et al. (Phys. Rev. Lett., vol. 110, 2013, 224502) discovered two spatially localized relative periodic solutions for pipe flow, which appeared in a saddle-node bifurcation at low Reynolds number. Combining slicing methods for continuous symmetry reduction with Poincaré sections for the first time in a shear flow setting, we compute and visualize the unstable manifold of the lower-branch solution and show that it extends towards the neighbourhood of the upper-branch solution. Surprisingly, this connection even persists far above the bifurcation point and appears to mediate the first stage of the puff generation: amplification of streamwise localized fluctuations. When the state-space trajectories on the unstable manifold reach the vicinity of the upper branch, corresponding fluctuations expand in space and eventually take the usual shape of a puff.

Long term storage in liquid nitrogen leads to only minor phenotypic and gene expression changes in the mammary carcinoma model cell line BT474 - Fazekas, Judit; Grunt, Thomas W.; Jensen-Jarolim, Erika; Singer, Josef (Oncotarget)
Background/Aim: Cancer cell lines are indispensible surrogate models in cancer research, as they can be used off-the-shelf, expanded to the desired extent, easily modified and exchanged between research groups for affirmation, reproduction or follow-up experiments. As malignant cells are prone to genomic instability, phenotypical changes may occur after certain passages in culture. Thus, cell lines have to be regularly authenticated to ensure data quality. In between experiments these cell lines are often stored in liquid nitrogen for extended time periods. Although freezing of cells is a necessary evil, little research is performed on how long-term storage affects cancer cell lines. Therefore, this study investigated the effects of a 28-year long liquid nitrogen storage period on BT474 cells with regard to phenotypical changes, differences in cell-surface receptor expression as well as cytokine and gene expressional variations. Methods: Two batches of BT474 cells, one frozen in 1986, the other directly purchased from ATCC were investigated by light microscopy, cell growth analysis, flow cytometry and cytokine as well as whole-transcriptome expression profiling. Results: The cell lines were morphologically indifferent and showed similar growth rates and similar cell-surface receptor expression. Transcriptome analysis revealed significant differences in only 26 of 40,716 investigated RefSeq transcripts with 4 of them being up-regulated and 22 down-regulated. Conclusion: This study demonstrates that even after very long periods of storage in liquid nitrogen, cancer cell lines display only minimal changes in their gene expression profiles. However, also such minor changes should be carefully assessed before continuation of experiments, especially if phenotypic alterations can be additionally observed.

Metadata for research data in practice - Petritsch, Barbara (Mitteilungen der Vereinigung Österreichischer Bibliothekarinnen & Bibliothekare)
What data is needed about data? Describing the process to answer this question for the institutional data repository IST DataRep.

Proof-of-personhood: Redemocratizing permissionless cryptocurrencies - Borge, Maria; Kokoris Kogias, Eleftherios; Jovanovic, Philipp; Gasser, Linus; Gailly, Nicolas; Ford, Bryan (2017 IEEE European Symposium on Security and Privacy Workshops)
Permissionless blockchain-based cryptocurrencies commonly use proof-of-work (PoW) or proof-of-stake (PoS) to ensure their security, e.g. to prevent double spending attacks. However, both approaches have disadvantages: PoW leads to massive amounts of wasted electricity and re-centralization, whereas major stakeholders in PoS might be able to create a monopoly. In this work, we propose proof-of-personhood (PoP), a mechanism that binds physical entities to virtual identities in a way that enables accountability while preserving anonymity. Afterwards we introduce PoPCoin, a new cryptocurrency, whose consensus mechanism leverages PoP to eliminate the dis-advantages of PoW and PoS while ensuring security. PoPCoin leads to a continuously fair and democratic wealth creation process which paves the way for an experimental basic income infrastructure.

CHAINIAC: Proactive software-update transparency via collectively signed skipchains and verified builds - Nikitin, Kirill; Kokoris Kogias, Eleftherios; Jovanovic, Philipp; Gasser, Linus; Gailly, Nicolas; Khoffi, Ismail; Cappos, Justin; Ford, Bryan (Proceedings of the 26th USENIX Conference on Security Symposium)
Software-update mechanisms are critical to the security of modern systems, but their typically centralized design presents a lucrative and frequently attacked target. In this work, we propose CHAINIAC, a decentralized software-update framework that eliminates single points of failure, enforces transparency, and provides efficient verifiability of integrity and authenticity for software-release processes. Independent witness servers collectively verify conformance of software updates to release policies, build verifiers validate the source-to-binary correspondence, and a tamper-proof release log stores collectively signed updates, thus ensuring that no release is accepted by clients before being widely disclosed and validated. The release log embodies a skipchain, a novel data structure, enabling arbitrarily out-of-date clients to efficiently validate updates and signing keys. Evaluation of our CHAINIAC prototype on reproducible Debian packages shows that the automated update process takes the average of 5 minutes per release for individual packages, and only 20 seconds for the aggregate timeline. We further evaluate the framework using real-world data from the PyPI package repository and show that it offers clients security comparable to verifying every single update themselves while consuming only one-fifth of the bandwidth and having a minimal computational overhead.

Scalable bias-resistant distributed randomness - Syta, E.; Jovanovic, P.; Kokoris Kogias, Eleftherios; Gailly, N.; Gasser, L.; Khoffi, I.; Fischer, M. J.; Ford, B. (2017 IEEE Symposium on Security and Privacy)
Bias-resistant public randomness is a critical component in many (distributed) protocols. Generating public randomness is hard, however, because active adversaries may behave dishonestly to bias public random choices toward their advantage. Existing solutions do not scale to hundreds or thousands of participants, as is needed in many decentralized systems. We propose two large-scale distributed protocols, RandHound and RandHerd, which provide publicly-verifiable, unpredictable, and unbiasable randomness against Byzantine adversaries. RandHound relies on an untrusted client to divide a set of randomness servers into groups for scalability, and it depends on the pigeonhole principle to ensure output integrity, even for non-random, adversarial group choices. RandHerd implements an efficient, decentralized randomness beacon. RandHerd is structurally similar to a BFT protocol, but uses RandHound in a one-time setup to arrange participants into verifiably unbiased random secret-sharing groups, which then repeatedly produce random output at predefined intervals. Our prototype demonstrates that RandHound and RandHerd achieve good performance across hundreds of participants while retaining a low failure probability by properly selecting protocol parameters, such as a group size and secret-sharing threshold. For example, when sharding 512 nodes into groups of 32, our experiments show that RandHound can produce fresh random output after 240 seconds. RandHerd, after a setup phase of 260 seconds, is able to generate fresh random output in intervals of approximately 6 seconds. For this configuration, both protocols operate at a failure probability of at most 0.08% against a Byzantine adversary.

Streaming algorithm for Euler characteristic curves of multidimensional images - Heiss, Teresa; Wagner, Hubert
We present an efficient algorithm to compute Euler characteristic curves of gray scale images of arbitrary dimension. In various applications the Euler characteristic curve is used as a descriptor of an image. Our algorithm is the first streaming algorithm for Euler characteristic curves. The usage of streaming removes the necessity to store the entire image in RAM. Experiments show that our implementation handles terabyte scale images on commodity hardware. Due to lock-free parallelism, it scales well with the number of processor cores. Additionally, we put the concept of the Euler characteristic curve in the wider context of computational topology. In particular, we explain the connection with persistence diagrams.

Thouless energy and multifractality across the many-body localization transition - Serbyn, Maksym; Zlatko, Papic; Abanin, Dmitry (Physical Review B - Condensed Matter and Materials Physics)
Thermal and many-body localized phases are separated by a dynamical phase transition of a new kind. We analyze the distribution of off-diagonal matrix elements of local operators across this transition in two different models of disordered spin chains. We show that the behavior of matrix elements can be used to characterize the breakdown of thermalization and to extract the many-body Thouless energy. We find that upon increasing the disorder strength the system enters a critical region around the many-body localization transition. The properties of the system in this region are: (i) the Thouless energy becomes smaller than the level spacing, (ii) the matrix elements show critical dependence on the energy difference, and (iii) the matrix elements, viewed as amplitudes of a fictitious wave function, exhibit strong multifractality. This critical region decreases with the system size, which we interpret as evidence for a diverging correlation length at the many-body localization transition. Our findings show that the correlation length becomes larger than the accessible system sizes in a broad range of disorder strength values and shed light on the critical behavior near the many-body localization transition.

Regulation of Drosophila hematopoietic sites by Activin-β from active sensory neurons - Makhijani, Kalpana; Alexander, Brandy; Rao, Deepti; Petraki, Sophia; Herboso, Leire; Kukar, Katelyn; Batool, Itrat; Wachner, Stephanie; Gold, Katrina; Wong, Corinna; O'Connor, Michael; Brückner, Katja (Nature Communications)
An outstanding question in animal development, tissue homeostasis and disease is how cell populations adapt to sensory inputs. During Drosophila larval development, hematopoietic sites are in direct contact with sensory neuron clusters of the peripheral nervous system (PNS), and blood cells (hemocytes) require the PNS for their survival and recruitment to these microenvironments, known as Hematopoietic Pockets. Here we report that Activin-β, a TGF-β family ligand, is expressed by sensory neurons of the PNS and regulates the proliferation and adhesion of hemocytes. These hemocyte responses depend on PNS activity, as shown by agonist treatment and transient silencing of sensory neurons. Activin-β has a key role in this regulation, which is apparent from reporter expression and mutant analyses. This mechanism of local sensory neurons controlling blood cell adaptation invites evolutionary parallels with vertebrate hematopoietic progenitors and the independent myeloid system of tissue macrophages, whose regulation by local microenvironments remain undefined.

Finding eigenvalues of self-maps with the Kronecker canonical form - Ethier, Marc; Jablonski, Grzegorz; Mrozek, Marian (Special Sessions in Applications of Computer Algebra)
Recent research has examined how to study the topological features of a continuous self-map by means of the persistence of the eigenspaces, for given eigenvalues, of the endomorphism induced in homology over a field. This raised the question of how to select dynamically significant eigenvalues. The present paper aims to answer this question, giving an algorithm that computes the persistence of eigenspaces for every eigenvalue simultaneously, also expressing said eigenspaces as direct sums of “finite” and “singular” subspaces.

Reactivation of the hippocampal cognitive map in goal-directed spatial tasks - Xu, Haibing
The hippocampus is a key brain region for memory and notably for spatial memory, and is needed for both spatial working and reference memories. Hippocampal place cells selectively discharge in specific locations of the environment to form mnemonic represen tations of space. Several behavioral protocols have been designed to test spatial memory which requires the experimental subject to utilize working memory and reference memory. However, less is known about how these memory traces are presented in the hippo campus, especially considering tasks that require both spatial working and long -term reference memory demand. The aim of my thesis was to elucidate how spatial working memory, reference memory, and the combination of both are represented in the hippocampus. In this thesis, using a radial eight -arm maze, I examined how the combined demand on these memories influenced place cell assemblies while reference memories were partially updated by changing some of the reward- arms. This was contrasted with task varian ts requiring working or reference memories only. Reference memory update led to gradual place field shifts towards the rewards on the switched arms. Cells developed enhanced firing in passes between newly -rewarded arms as compared to those containing an unchanged reward. The working memory task did not show such gradual changes. Place assemblies on occasions replayed trajectories of the maze; at decision points the next arm choice was preferentially replayed in tasks needing reference memory while in the pure working memory task the previously visited arm was replayed. Hence trajectory replay only reflected the decision of the animal in tasks needing reference memory update. At the reward locations, in all three tasks outbound trajectories of the current arm were preferentially replayed, showing the animals’ next path to the center. At reward locations trajectories were replayed preferentially in reverse temporal order. Moreover, in the center reverse replay was seen in the working memory task but in the other tasks forward replay was seen. Hence, the direction of reactivation was determined by the goal locations so that part of the trajectory which was closer to the goal was reactivated later in an HSE while places further away from the goal were reactivated earlier. Altogether my work demonstrated that reference memory update triggers several levels of reorganization of the hippocampal cognitive map which are not seen in simpler working memory demand s. Moreover, hippocampus is likely to be involved in spatial decisions through reactivating planned trajectories when reference memory recall is required for such a decision.

(The exact security of) Message authentication codes - Rybar, Michal
In this thesis we discuss the exact security of message authentications codes HMAC , NMAC , and PMAC . NMAC is a mode of operation which turns a fixed input-length keyed hash function f into a variable input-length function. A practical single-key variant of NMAC called HMAC is a very popular and widely deployed message authentication code (MAC). PMAC is a block-cipher based mode of operation, which also happens to be the most famous fully parallel MAC. NMAC was introduced by Bellare, Canetti and Krawczyk Crypto’96, who proved it to be a secure pseudorandom function (PRF), and thus also a MAC, under two assumptions. Unfortunately, for many instantiations of HMAC one of them has been found to be wrong. To restore the provable guarantees for NMAC , Bellare [Crypto’06] showed its security without this assumption. PMAC was introduced by Black and Rogaway at Eurocrypt 2002. If instantiated with a pseudorandom permutation over n -bit strings, PMAC constitutes a provably secure variable input-length PRF. For adversaries making q queries, each of length at most ` (in n -bit blocks), and of total length σ ≤ q` , the original paper proves an upper bound on the distinguishing advantage of O ( σ 2 / 2 n ), while the currently best bound is O ( qσ/ 2 n ). In this work we show that this bound is tight by giving an attack with advantage Ω( q 2 `/ 2 n ). In the PMAC construction one initially XORs a mask to every message block, where the mask for the i th block is computed as τ i := γ i · L , where L is a (secret) random value, and γ i is the i -th codeword of the Gray code. Our attack applies more generally to any sequence of γ i ’s which contains a large coset of a subgroup of GF (2 n ). As for NMAC , our first contribution is a simpler and uniform proof: If f is an ε -secure PRF (against q queries) and a δ - non-adaptively secure PRF (against q queries), then NMAC f is an ( ε + `qδ )-secure PRF against q queries of length at most ` blocks each. We also show that this ε + `qδ bound is basically tight by constructing an f for which an attack with advantage `qδ exists. Moreover, we analyze the PRF-security of a modification of NMAC called NI by An and Bellare that avoids the constant rekeying on multi-block messages in NMAC and allows for an information-theoretic analysis. We carry out such an analysis, obtaining a tight `q 2 / 2 c bound for this step, improving over the trivial bound of ` 2 q 2 / 2 c . Finally, we investigate, if the security of PMAC can be further improved by using τ i ’s that are k -wise independent, for k > 1 (the original has k = 1). We observe that the security of PMAC will not increase in general if k = 2, and then prove that the security increases to O ( q 2 / 2 n ), if the k = 4. Due to simple extension attacks, this is the best bound one can hope for, using any distribution on the masks. Whether k = 3 is already sufficient to get this level of security is left as an open problem. Keywords: Message authentication codes, Pseudorandom functions, HMAC, PMAC.

Brittle fracture simulation with boundary elements for computer graphics - Hahn, David
This thesis describes a brittle fracture simulation method for visual effects applications. Building upon a symmetric Galerkin boundary element method, we first compute stress intensity factors following the theory of linear elastic fracture mechanics. We then use these stress intensities to simulate the motion of a propagating crack front at a significantly higher resolution than the overall deformation of the breaking object. Allowing for spatial variations of the material's toughness during crack propagation produces visually realistic, highly-detailed fracture surfaces. Furthermore, we introduce approximations for stress intensities and crack opening displacements, resulting in both practical speed-up and theoretically superior runtime complexity compared to previous methods. While we choose a quasi-static approach to fracture mechanics, ignoring dynamic deformations, we also couple our fracture simulation framework to a standard rigid-body dynamics solver, enabling visual effects artists to simulate both large scale motion, as well as fracturing due to collision forces in a combined system. As fractures inside of an object grow, their geometry must be represented both in the coarse boundary element mesh, as well as at the desired fine output resolution. Using a boundary element method, we avoid complicated volumetric meshing operations. Instead we describe a simple set of surface meshing operations that allow us to progressively add cracks to the mesh of an object and still re-use all previously computed entries of the linear boundary element system matrix. On the high resolution level, we opt for an implicit surface representation. We then describe how to capture fracture surfaces during crack propagation, as well as separate the individual fragments resulting from the fracture process, based on this implicit representation. We show results obtained with our method, either solving the full boundary element system in every time step, or alternatively using our fast approximations. These results demonstrate that both of these methods perform well in basic test cases and produce realistic fracture surfaces. Furthermore we show that our fast approximations substantially out-perform the standard approach in more demanding scenarios. Finally, these two methods naturally combine, using the full solution while the problem size is manageably small and switching to the fast approximations later on. The resulting hybrid method gives the user a direct way to choose between speed and accuracy of the simulation.

Computational topology for structural molecular biology - Edelsbrunner, Herbert; Koehl, Patrice (Handbook of Discrete and Computational Geometry, Third Edition)
The advent of high-throughput technologies and the concurrent advances in information sciences have led to a data revolution in biology. This revolution is most significant in molecular biology, with an increase in the number and scale of the “omics” projects over the last decade. Genomics projects, for example, have produced impressive advances in our knowledge of the information concealed into genomes, from the many genes that encode for the proteins that are responsible for most if not all cellular functions, to the noncoding regions that are now known to provide regulatory functions. Proteomics initiatives help to decipher the role of post-translation modifications on the protein structures and provide maps of protein-protein interactions, while functional genomics is the field that attempts to make use of the data produced by these projects to understand protein functions. The biggest challenge today is to assimilate the wealth of information provided by these initiatives into a conceptual framework that will help us decipher life. For example, the current views of the relationship between protein structure and function remain fragmented. We know of their sequences, more and more about their structures, we have information on their biological activities, but we have difficulties connecting this dotted line into an informed whole. We lack the experimental and computational tools for directly studying protein structure, function, and dynamics at the molecular and supra-molecular levels. In this chapter, we review some of the current developments in building the computational tools that are needed, focusing on the role that geometry and topology play in these efforts. One of our goals is to raise the general awareness about the importance of geometric methods in elucidating the mysterious foundations of our very existence. Another goal is the broadening of what we consider a geometric algorithm. There is plenty of valuable no-man’s-land between combinatorial and numerical algorithms, and it seems opportune to explore this land with a computational-geometric frame of mind.

Fast hole tunneling times in germanium hut wires probed by single-shot reflectometry - Vukusic, Lada; Kukucka, Josip; Watzinger, Hannes; Katsaros, Georgios (Nano Letters)
Heavy holes confined in quantum dots are predicted to be promising candidates for the realization of spin qubits with long coherence times. Here we focus on such heavy-hole states confined in germanium hut wires. By tuning the growth density of the latter we can realize a T-like structure between two neighboring wires. Such a structure allows the realization of a charge sensor, which is electrostatically and tunnel coupled to a quantum dot, with charge-transfer signals as high as 0.3 e. By integrating the T-like structure into a radiofrequency reflectometry setup, single-shot measurements allowing the extraction of hole tunneling times are performed. The extracted tunneling times of less than 10 μs are attributed to the small effective mass of Ge heavy-hole states and pave the way toward projective spin readout measurements.

On the marked length spectrum of generic strictly convex billiard tables - Huang, Guan; Kaloshin, Vadim; Sorrentino, Alfonso (Duke Mathematical Journal)
In this paper we show that for a generic strictly convex domain, one can recover the eigendata corresponding to Aubry–Mather periodic orbits of the induced billiard map from the (maximal) marked length spectrum of the domain.

Dynamical spectral rigidity among Z2-symmetric strictly convex domains close to a circle - De Simoi, Jacopo; Kaloshin, Vadim; Wei, Qiaoling (Annals of Mathematics)
We show that any sufficiently (finitely) smooth ℤ₂-symmetric strictly convex domain sufficiently close to a circle is dynamically spectrally rigid; i.e., all deformations among domains in the same class that preserve the length of all periodic orbits of the associated billiard flow must necessarily be isometric deformations. This gives a partial answer to a question of P. Sarnak.

Mitochondrial ADP/ATP carrier in dodecylphosphocholine binds cardiolipins with non-native affinity - Dehez, François; Schanda, Paul; King, Martin S.; Kunji, Edmund R.S.; Chipot, Christophe (Biophysical Journal)
Biophysical investigation of membrane proteins generally requires their extraction from native sources using detergents, a step that can lead, possibly irreversibly, to protein denaturation. The propensity of dodecylphosphocholine (DPC), a detergent widely utilized in NMR studies of membrane proteins, to distort their structure has been the subject of much controversy. It has been recently proposed that the binding specificity of the yeast mitochondrial ADP/ATP carrier (yAAC3) toward cardiolipins is preserved in DPC, thereby suggesting that DPC is a suitable environment in which to study membrane proteins. In this communication, we used all-atom molecular dynamics simulations to investigate the specific binding of cardiolipins to yAAC3. Our data demonstrate that the interaction interface observed in a native-like environment differs markedly from that inferred from an NMR investigation in DPC, implying that in this detergent, the protein structure is distorted. We further investigated yAAC3 solubilized in DPC and in the milder dodecylmaltoside with thermal-shift assays. The loss of thermal transition observed in DPC confirms that the protein is no longer properly folded in this environment.
Keywords: Biophysics

Slow conformational exchange and overall rocking motion in ubiquitin protein crystals - Kurauskas, Vilius; Izmailov, Sergei A.; Rogacheva, Olga N.; Hessel, Audrey; Ayala, Isabel; Woodhouse, Joyce; Shilova, Anastasya; Xue, Yi; Yuwen, Tairan; Coquelle, Nicolas; Colletier, Jacques-Philippe; Skrynnikov, Nikolai R.; et al. (Nature Communications)
Proteins perform their functions in solution but their structures are most frequently studied inside crystals. Here we probe how the crystal packing alters microsecond dynamics, using solid-state NMR measurements and multi-microsecond MD simulations of different crystal forms of ubiquitin. In particular, near-rotary-resonance relaxation dispersion (NERRD) experiments probe angular backbone motion, while Bloch–McConnell relaxation dispersion data report on fluctuations of the local electronic environment. These experiments and simulations reveal that the packing of the protein can significantly alter the thermodynamics and kinetics of local conformational exchange. Moreover, we report small-amplitude reorientational motion of protein molecules in the crystal lattice with an ~3–5° amplitude on a tens-of-microseconds time scale in one of the crystals, but not in others. An intriguing possibility arises that overall motion is to some extent coupled to local dynamics. Our study highlights the importance of considering the packing when analyzing dynamics of crystalline proteins.

Solid‐state NMR H–N–(C)–H and H–N–C–C 3D/4D correlation experiments for resonance assignment of large proteins - Fraga, Hugo; Arnaud, Charles‐Adrien; Gauto, Diego F.; Audin, Maxime; Kurauskas, Vilius; Macek, Pavel; Krichel, Carsten; Guan, Jia‐Ying; Boisbouvier, Jerome; Sprangers, Remco; Breyton, Cécile; Schanda, Paul (ChemPhysChem)
Solid‐state NMR spectroscopy can provide insight into protein structure and dynamics at the atomic level without inherent protein size limitations. However, a major hurdle to studying large proteins by solid‐state NMR spectroscopy is related to spectral complexity and resonance overlap, which increase with molecular weight and severely hamper the assignment process. Here the use of two sets of experiments is shown to expand the tool kit of 1H‐detected assignment approaches, which correlate a given amide pair either to the two adjacent CO–CA pairs (4D hCOCANH/hCOCAcoNH), or to the amide 1H of the neighboring residue (3D HcocaNH/HcacoNH, which can be extended to 5D). The experiments are based on efficient coherence transfers between backbone atoms using INEPT transfers between carbons and cross‐polarization for heteronuclear transfers. The utility of these experiments is exemplified with application to assemblies of deuterated, fully amide‐protonated proteins from approximately 20 to 60 kDa monomer, at magic‐angle spinning (MAS) frequencies from approximately 40 to 55 kHz. These experiments will also be applicable to protonated proteins at higher MAS frequencies. The resonance assignment of a domain within the 50.4 kDa bacteriophage T5 tube protein pb6 is reported, and this is compared to NMR assignments of the isolated domain in solution. This comparison reveals contacts of this domain to the core of the polymeric tail tube assembly.
Keywords: Physical and Theoretical Chemistry; Atomic and Molecular Physics; and Optics